Effect of different treatment of sugarcane fiber on mechanical properties, morphology and swelling behavior of Low density Polyethylene (LDPE) composites - Zamzarina Hasim (Universiti Malaysia Perlis, 2008)
The sugarcane bagasse is a residue widely generated in high proportions in the agroindustry. In this research, the bagasse fiber has been used as reinforcing component for polyethylene. The chemical treatments using sodium hydroxide (NaOH) and maleic acid (MA) were carried out to modify the fiber properties. The effects of different chemical contents on the composites were investigated. Generally, treated fibers composites have superior mechanical properties than the untreated fibers composites. NaOH treated fiber composite show better improvement compared to MA treated fiber. Morphology investigations show that the surface modifications improve the fiber-matrix interaction. In the general, it was observed that the treated fiber composites show lower water absorption properties compared to those of untreated fiber composites.